Analysis of Lean Manufacturing Using the Waste Assessment Model (WAM) to Reduce Waste in the Bolt Production Process at PT.XYZ - Sinulingga, Irma Dani Br; Rusindiyanto (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
PT.XYZ was established in 1975 and is a manufacturer of bolts, nuts, anchor bolts, stud bolts, tapping screws, and washers in Southeast Asia, with an annual production capacity of 48,000 tons. These products serve various industries such as construction, manufacturing, automotive, and general industries. Despite careful planning, challenges in large production volumes and varied product specifications remain obstacles in meeting customer demand. Amidst global competition and stringent industry standards, implementing lean manufacturing is crucial to enhance efficiency and competitiveness. This study aims to identify waste ≤ 17% using the Waste Assessment Model, conduct Root Cause Analysis to pinpoint waste origins, and propose improvement strategies using 5W+1H Analysis. Findings reveal Inventory (21.44%) as the highest waste contributor, attributed to interdepartmental coordination issues, production errors, lack of operator focus, delayed resource availability, and production flow bottlenecks. Additionally, Defects (18.47%) arise from excessive workload on production operators. Improvement recommendations include enhancing interdepartmental coordination, refining production scheduling, evaluating production processes, and conducting training and evaluations to enhance operator skills.